Correlation of low fetal fraction of cell-free DNA at the early second-trimester and pregnancy complications related to placental dysfunction in twin pregnancy - Li, Jiaxin; Gu, Xunke; Wei, Yuan; Tao, Yuan; Zhai, Bingbing; Peng, Chunfang; Huang, Quanfei; Deng, Tao; Yuan, Pengbo (Frontiers in Medicine, 2022)
This study aimed to determine the correlation between fetal fraction (FF) of cell-free DNA (cf-DNA) and pregnancy complications related to placental dysfunction in Twin Pregnancy. This retrospective cohort study analyzed twin pregnant women who underwent noninvasive prenatal testing (NIPT) at 12+0–26+6 weeks of gestation from April 2017 to April 2021. Low fetal fraction (LFF) was defined as individually less than the 25th, 10th, 5th, and 2.5th percentile among all fetal fractions in the cohort. Primary outcomes included gestational hypertension (GH), preeclampsia (PE), gestational diabetes mellitus (GDM), and small for gestational age (SGA). Logistic regression analysis was used to assess the relationship between LFF and pregnancy complications. A total of 500 twin pregnancies (male-male twins, 245; female-female twins, 255) were included in this study. In LFF group (FF < 25th percentiles), maternal BMI was significantly higher than FF > 75th percentiles (23.6 kg/m2 vs. 21.3 kg/m2; P < 0.001). The risk of SGA increased gradually from FF < 25th percentiles (adjusted odds ratio [OR], 1.71; 95% confidence interval [CI], 1.07–2.99; P = 0.016) to FF < 2.5th percentiles (adjusted OR, 4.44; 95% CI, 1.33–14.82; P = 0.015). In addition, the risks of SGA in both two fetuses were higher than at least one fetus SGA in LFF group. LFF had no correlation with GH, PE, and GDM in twin pregnancy. In conclusion, LFF has a strong association with increased risk of SGA in twin pregnancy. Moreover, FF of cf-DNA may provide a new idea for the early screening of diseases related to placental dysfunction in twin pregnancy.